2010
DOI: 10.5194/bgd-7-8123-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-ubiquity of ice-edge blooms in the Arctic

Abstract: Ice-edge blooms are significant features of Arctic primary production, yet have received relatively little attention. Here we combine satellite ocean colour and sea-ice data in a pan-Arctic study. Ice-edge blooms occur in all seasonally ice-covered areas and from spring to late summer, being observed in 77–89% of locations for which adequate data exist, and usually peaking within 20 days of ice retreat. They sometimes form long belts along the Ice-edge (greater than 100 km), although smaller structures were al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…In the Arctic, ice edge blooms seem to be frequent, typically last 20 days in a 100 km band near the ice edge, but may last longer in some instances [Perrette et al, 2011]. As they are transient in space and time, quantifying their contribution to overall production is challenging.…”
Section: Light Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Arctic, ice edge blooms seem to be frequent, typically last 20 days in a 100 km band near the ice edge, but may last longer in some instances [Perrette et al, 2011]. As they are transient in space and time, quantifying their contribution to overall production is challenging.…”
Section: Light Transmissionmentioning
confidence: 99%
“…Observations indicate: (i) phytoplankton blooms start under the ice [e.g., Arrigo et al, 2012] and then typically follow the summer ice retreat in the Arctic [Perrette et al, 2011], while only ice-edge blooms have been reported in the Southern Ocean [Smith and Nelson, 1985]; (ii) recent Arctic Ocean sea ice retreat is associated with a significant increase in pelagic primary production [Arrigo et al, 2008b;Tremblay et al, 2011]; and (iii) marine ecosystem shifts have occurred due to changing sea ice conditions, notably in the Bering Sea (Arctic) [Grebmeier et al, 2006] These observations support a significant role for sea ice on water column primary productivity, which can be mediated by physical and biogeochemical processes. First, sea ice, the material it contains (organic matter and sediments), and its snow cover control the incoming light in the upper ocean; while ice growth and melt affect the upper ocean stratification and nutrient supply [Tremblay and Gagnon, 2009].…”
Section: Biological Interactions With the Water Columnmentioning
confidence: 99%
“…A record minimum of 4.2 million km 2 was recorded in September 2007 (e.g., Perovich et al, 2008) compared to a 1979-2000 mean of 7.0 million km 2 . Given ongoing anthropogenic climate change, this trend is likely to continue, with modelling studies predicting a seasonally ice-free Arctic Ocean (AO) as early as 2050 (Vinnikov et al, 1999;Flato and Boer, 2001;Overland et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, both the Arctic ice and plankton algae blooms start earlier (Kahru et al, 2011;Perrette et al, 2011) . Seasonality in bloom development and in downward carbon export in present-day climate and ice conditions (a), and a future warmer climate with thinner ice in winter and more melting of summer ice, causing a widening of the seasonal ice zone (B).…”
Section: Goal and Intentionsmentioning
confidence: 99%